A marketing perspective on e-commerce in an MNC - Kotka, Kristian (My University, 2019)
The rapidly evolving digital environment has made online shopping an established form of shopping behavior in various industries. In this regard, the role of the consumer has become more empowered, and the digital environment and e-commerce have become essential aspects in an MNC’s marketing strategies. In this relation the implementation aspect of the strategy and the marketing tactics involved have remained an interesting research topic in the academic world. The study examines e-commerce in a multinational company context from a strategic marketing perspective. The study was conducted as a qualitative intensive single case study. The data collection of the study consisted of interviews which were supported by company-specific documents. The theoretical framework of the study combines literature from international marketing strategy, e-commerce, digital marketing mix and the consumer journey. The findings of the study were similar to those presented in the framework. The connection between the digital marketing mix elements and the consumer journey was supported and the marketing mix’s role as a more consumer-centric tool was seconded. In this regard, the findings highlighted the promotion and place elements in relation to the consumer journey framework. The findings regarding the standardization and adaptation aspect of e-commerce decisions highlighted that control and planning are key aspects regarding standardization whereas consumer behavior was found a key factor driving adaptation in e-commerce decisions.
Keywords: MNC, standardization, adaptation, e-commerce, digital marketing, marketing mix, consumer journey